2021
DOI: 10.1002/eji.202049065
|View full text |Cite
|
Sign up to set email alerts
|

Non‐zero‐sum microbiome immune system interactions

Abstract: Fundamental asymmetries between the host and its microbiome in enzymatic activities and nutrient storage capabilities have promoted mutualistic adaptations on both sides. As a result, the enteric immune system has evolved so as not to cause a zero-sum sterilization of non-self, but rather achieve a non-zero-sum self-reinforcing cooperation with its evolutionary partner the microbiome. In this review, we attempt to integrate the accumulated knowledge of immune-microbiome interactions into an evolutionary framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 207 publications
0
2
0
Order By: Relevance
“…The development and function of colonic innate and adaptive immune cell populations are strongly influenced by the presence of the microbiota ( Gury-BenAri et al, 2016 ; Honda and Littman, 2016 ; Tuganbaev and Honda, 2021 ). However, the frequency of colonic IL-4 + ILC2s and their transcriptional profiles were not affected by the absence of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The development and function of colonic innate and adaptive immune cell populations are strongly influenced by the presence of the microbiota ( Gury-BenAri et al, 2016 ; Honda and Littman, 2016 ; Tuganbaev and Honda, 2021 ). However, the frequency of colonic IL-4 + ILC2s and their transcriptional profiles were not affected by the absence of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiome can affect the function and number of enteric neurons (8)(9)(10), and the early gut microbiota plays an important role in the development of the ENS after birth (11,12). Several studies have shown that abnormalities in the myenteric plexus and a decrease of intestinal motility can be observed in early postnatal germ-free mice (11).…”
Section: Introductionmentioning
confidence: 99%